HBV-DNA levels predict overall mortality in HIV/HBV coinfected individuals. - Nikolopoulos, Georgios K; Paraskevis, Dimitrios; Psichogiou, Mina; Hatzakis, Angelos (J Med Virol, 2016)
The coinfection of Hepatitis B virus (HBV) and human immunodeficiency virus (HIV) has been associated with increased death rates. However, the relevant research has mostly relied on serologic HBV testing [HBV surface antigen (HBsAg)]. The aim of this work was to explore the relationship of HBV viraemia with overall mortality among HIV/HBV coinfected individuals. The analysis included 1,609 HIV seropositives of a previously described cohort (1984-2003) with limited exposure to tenofovir (12%) and a median follow-up of approximately 5 years. Those with persistent expression of HBsAg were further tested for HBV-DNA. The data were analyzed using Poisson regression models. Totally, 101 participants were chronic carriers of HBsAg (6.28%). Of these, 81 were tested for HBV-DNA. The median HBV-DNA levels were 3.81 log (base-10) International Units (IU)/ml. A third (31%) of those tested for HBV-DNA had received tenofovir. Before developing acquired immune deficiency syndrome (AIDS), the adjusted incidence rate ratio (IRR) for all-cause mortality of coinfected patients with HBV viraemia above the median value versus the HIV monoinfected group was 3.44 [95% confidence interval (CI): 1.05-11.27]. Multivariable regressions in the coinfected group only (n = 81) showed that one log-10 increase in HBV-DNA levels was associated with an elevated risk for death (IRR: 1.24, 95%CI: 1.03-1.49). HBV-DNA levels predict overall mortality in the setting of HIV/HBV coinfection, especially during the period before developing AIDS, and could thus help prioritize needs and determine the frequency of medical monitoring.
Keywords: CD4 Lymphocyte Count; Coinfection; DNA, Viral; Female; Follow-Up Studies; Hepatitis B; Hepatitis B Surface Antigens; Hepatitis B virus; HIV Infections; HIV-1; Humans; Male; Middle Aged; Poisson distribution; Viral Load; Viremia